THE ROLE OF CUSTOMER SERVICE MANAGEMENT IN THE SUCCESS OF DIGITAL MARKETING PLANS IN IRAQ (ASIA CELL COMMUNICATIONS COMPANY) - Turkan Hussein Daoud (Scholars Digest Publishing, 2025)
This article looks at the role of customer service management on the adoption of digital marketing strategies within Asia Cell Communications Company. Using a descriptive analysis of the variables considered in the study, the results show customer service management was generally rated at moderate to highly (overall mean = 3.75, SD = 0.419) and the mean ratings of the sub-variables reflected the focus on rapid-response and communication quality (mean = 3.80), understanding customer needs to help develop closer relationships with customers (mean = 3.75), problem solving (mean = 3.72), and staff efficiency (mean = 3.70). Commonly rated as the largest influence on digital marketing performance was the perceived ability of the telecommunications company to achieve campaign goals (mean = 3.85) and increased customer satisfaction levels (mean = 3.82). The regression analysis provided evidence to suggest that customer service management was statistically significant and positively related to digital marketing effectiveness demonstrating that customer service management explained 64.8% of variance (R² = 0.648, value of p < 0.001). In regard to the sub-variables, rapid-response (β = 0.810) had the largest effect found in this study, which was followed by staff efficiency, communication quality, understanding customer needs and problem solving. All of the main and sub-hypotheses were met and embraced by the results of this material.